2014
DOI: 10.1007/s10900-014-9945-4
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obesity Perceptions Among African American Caregivers in a Rural Georgia Community: A Mixed Methods Approach

Abstract: Given the pivotal role of African American caregiver's perceptions of childhood obesity in rural areas, the inclusion of caregiver's perceptions could potentially reduce childhood obesity rates. The objective of the current study was to explore childhood obesity perceptions among African Americans in a rural Georgia community. This concurrent mixed methods study utilized two theoretical frameworks: Social Cognitive Theory and Social Ecological Model. Using a convenience sample, caregivers ages 22-65 years comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Counties with more African American population rank lower on health across all county types. This was expected, as communities with more African American population have lower health outcomes [37] and lower life expectancy [54]. However, model results show two surprises: counties with more Hispanics have higher community health across all county types, and counties with more White poverty have lower health.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Counties with more African American population rank lower on health across all county types. This was expected, as communities with more African American population have lower health outcomes [37] and lower life expectancy [54]. However, model results show two surprises: counties with more Hispanics have higher community health across all county types, and counties with more White poverty have lower health.…”
Section: Discussionmentioning
confidence: 87%
“…For example, a meta-analysis [36] reported an association between planning, transportation, and physical environment (such as parks and trails), on adults' and children's physical activity. In US nonmetropolitan communities, more outdoor recreation facilities are related to a lower prevalence of obesity among both children [37], and adults [38]. Even a state level variable, such as suburban sprawl, has been associated with the rise in obesity in the US since the 1990s [39].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers in one study believed that parents played the most important role in contributing to child weight status (Alexander, Alfonso, & Hansen, 2015). Previous quantitative and qualitative research has also found that AA youth preferred tangible or instrumental support from parents to improve lifestyle behaviors (Siceloff, Wilson, & Van Horn, 2014; Wright, Wilson, Griffin, & Evans, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Six studies examined parents' perception regarding the risk factors of childhood obesity, parents perceived that genetic factors, less vegetable-consumption, low physical activity as key risk factors of childhood obesity 15 . Further, three studies revealed that parents perceived environmental factors such as poorly built environmental conditions, unsafe, dangerous environments, environmental barriers, and poorly maintained sidewalks had increased odds of being obese 41,39,49 . Other studies showed that parents perceived that low physical activity and additional hours of watching television as risk factors of childhood obesity 40 .…”
Section: Parents' Perception Regarding Risk Factors and Health Concermentioning
confidence: 99%